Determination of weight loss methods and effects among wrestlers before an official championship - Seker, R.; Isik, O.; Durukan, E.; Eraslan, M.; Talaghir, L.-G.; Dorgan, V. (Frontiers in Nutrition, 2024)
Introduction: It is known that combat athletes frequently lose weight before a competition. This study aimed to determine the weight loss methods before an official championship and the effects of these weight loss methods on the performance of wrestlers.